Realidades y Perspectivas del primer Centro de Acogida Especializado en la Atención de Menores vinculados al VIH/SIDA en Chile - Alicia Nifuri; Roberto Polanco - Carrasco (CAEN, 2007)
The number of patients infected with HIV/AIDS has increased maintainedly in the last decade, transforming itself into one of the main causes of death in the world, specially among young people and countries with limited resources. Nowadays, the new medicines and treatments manage to make the virus. indetectable in blood, stopping this way, the inmunological system deterioration and recovering qualitatively and quantitatively the immune response. This fact, forces the modern therapies must be held for as long as lifetime is, being interesting that nowadays, we speak of a HIV/AIDS as a chronic disease, this substantially changes the clinical intervention focus if we compare it with the focus that prevailed at the beggining of this pandemia.. The present report made in 1997, is reedited today, in order to contribute to the construction of an historical perspective of professional intervention in HIV/AIDS in Chile. In this work, are outlined, the challenges and difficulties that must be confronted at a center of welcome for the work with HIV Positive children, information that could be considered useful to appreciate the evolution of these challenges, after one decade of intervention.